Pelatihan Pemijahan Ikan dengan Metode Kawin Suntik dan Pengkayaan Pakan dengan Tepung Kunyit di SMKN 1 Sebatik Barat, Kabupaten Nunukan - Kartina, Kartina; Awaludin, Awaludin; Sanda Lembang, Miska; Nasra, Nasra; .S, Salman; Zainuddin, Zainuddin; Nurasmi, Nurasmi; Dyta Nugraeni, Christine; Gandri Haryono, M.; Alawiyah, Alawiyah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Catfish (Clarias sp.) is one of the freshwater commodities that is favored because of its high economic value, rich in protein, can be cultivated in narrow land or yards and of course much in demand by the public. Efforts to develop in cultivation continue to be made, including an increase in seed production. The purpose of this activity is to provide training to partners in this case are students of the Department of Fisheries Cultivation, SMKN 1 Sebatik Barat regarding the semi-artificial spawning system (injection mating) and enrichment of feed with turmeric flour to support increased production and quality of catfish seeds. The methods used are socialization and counseling with lectures, hands-on practice related to injecting mating techniques with ovaprim hormone and making feed enriched with turmeric flour. The results of the activity showed an increase in partner knowledge regarding the benefits of turmeric and the role of hormone use in hatchery activities. In addition, partners have also been able to select gonadally mature broodstock, make feed enriched with turmeric flour and perform injection mating of catfish with hormones appropriately. The hope for follow-up is that partners can apply the techniques that have been learned for hatchery activities so that the scarcity of seeds, especially in West Sebatik, can be overcome and no longer have to bring in from outside